Gambaran Gaya Hidup Penderita Hipertensi Di Klinik Dokter Wulan Demak - Nadia Amalia; Iskim Lutfha; Moch Aspihan; Abrori (STIKes Ibnu Sina Ajibarang, 2025)
Hypertension is a condition where a person experiences high blood pressure, especially above 140/90 mmHg, and can cause stroke in around 60% of sufferers. To control hypertension and its complications, it is important to reduce risky behaviors. Prevention and control of risk factors can be done through healthy lifestyle changes. However, a survey conducted at the Dr. Clinic. Wulan Demak shows that many hypertension sufferers do not adopt a healthy lifestyle, such as not getting enough physical activity, poor diet, smoking and lack of sleep. This type of research is quantitative research, with a descriptive research design. The sampling technique used the Probability sampling method using the Slovin formula and the sample size was 150 respondents who met the inclusion criteria, namely 1) Patients suffering from hypertension 2) Patients who agreed to be respondents 3) Having a systolic blood pressure classification of >130 mmHg and diastolic blood pressure > 80 mmHg. 4) Patients who can communicate well. Data collection methods used IPAQ, FFQ, PSQI and Smoking History questionnaires. The data analysis used is univariate analysis to find the frequency distribution of each data. The characteristics of respondents from the results of the study were obtained that the majority were female with a total of 94 respondents (62.7%). The majority of respondents were aged 46 to 65 years as many as 109 respondents (72.7%). The majority of respondents with no education were 77 respondents (51.3). The majority of respondents worked as housewives as many as 83 respondents (55.3%). The majority of respondents had high blood pressure at HT Stage I as many as 117 respondents (78.0%). The majority of moderate physical activity with a total of 81 people (54.0%), the majority of poor diet with a total of 115 respondents (76.7%), the majority had bad sleeping habits with a total of 103 respondents (68.7%), and the majority did not smoke with a total of 107 people (71.3%). The lifestyle of hypertension sufferers is mostly moderate physical activity, poor diet, bad sleeping habits and did not smoke.